English Language Proficiency in Medical Education: Exploring Performance Variations Between Undergraduate and Postgraduate Students (Faridpur Medical College Journal, 2026)
Background: English proficiency is crucial for medical students to comprehend textbooks, lectures, and academic materials, particularly in Anatomy, which involves complex texts and terminology. Bangladeshi medical students often face difficulties in academic reading and grammar, potentially affecting learning outcomes. Aim of this study was to assess and compare the English language proficiency of undergraduate and postgraduate medical students and examine its impact on their academic performance.Materials & Methods: A descriptive cross-sectional study was conducted at the Department of Anatomy, BMU, Dhaka, from January to December 2021. A total of 181 participants were included: 121 first-year MBBS undergraduates (Group A) from one government and one private medical college in Dhaka, and 60 postgraduate students/residents enrolled in MPhil/MS Anatomy courses (Group B).Result: Postgraduate students outperformed undergraduates in most academic reading tasks, e.g., factual questions (56.7% vs. 40.3%), inference (50.6% vs. 26.2%), and sentence simplification (62.8% vs. 52.0%). Vocabulary (29.2% vs. 27.3%) and reference questions (30.0% vs. 29.7%) showed similar performance. In grammar, postgraduates scored higher in conjunctions (59.4% vs. 46.3%), collocations (78.3% vs. 71.1%), and past participle forms (87.5% vs. 63.2%), whereas both groups struggled with connectors, prepositions, and keyword transformations.Conclusion: The study underscores the importance of tailored English language support to enhance medical students’ comprehension of Anatomy texts and improve academic performance.Faridpur Med. Coll. J. 2026;21(2): 38-43